Ribeirinhos da Amazônia: dinâmica territorial na Comunidade Canauini no Baixo Rio Branco-Roraima - Maia, Rafael Oliveira da Silva (2021)
The Canauini riverside community is one of seven communities belonging to the municipality of Caracaraí. Located in the region called Baixo Rio Branco in the south of the State of Roraima, within the perimeter of the Rio Preto tract and the Territory of the Xeruini Environmental Protection Area (APA). The community has already undergone countless socio-territorial transformations due to changes in geographic location, space-transforming agents and water cycles in the Lower Rio Branco. Thus, this dissertation had the general objective of understanding the socio-territorial dynamics of the Community, having as theoretical support the concepts of Territory, Territoriality and Riverside Community in three dimensions: Territory / Territoriality, Economic and Cultural. The method adopted was of a descriptive and exploratory character, seeking to adopt a perspective of totality in order to understand the socio- territorial dynamics of the place, through the case study and orality. Two fieldwork was carried out using technical and instrumental procedures such as questionnaires, semi-structured interviews, direct observation in places where economic, religious and sporting activities take place and informal conversations (oral narrative), as well as the use of the positioning system (GPS), photographic and audiovisual records and bibliographic and documentary survey. Based on information collected and thematic maps, tables and graphs, it was possible to understand the socio-territorial dynamics of the community, considering the territorialities of the riverside inhabitants. The results showed us the geohistory of the Community, the circuits of lives, its form of organization, the population and economic aspects as well as the life of this community.